Transitions and Diversity in Didactics: An Exploration Searching for Implications for Vocational Education and Training - Moreno Herrera, Lázaro (International Journal for Research in Vocational Education and Training, 2015)
Depending on the perspective and even language, the concept of didactics is defined in different ways. The debate about conceptualization, particularly concerning the equivalence in English of what in other languages, specifically Germanic and Latin languages, is termed "didactics" is well documented in the research literature. There is a claim in this article concerning the need to transcend the language discussion; it is indeed necessary, especially for Vocational Education & training (VET), to develop a close linkage between what some authors consider "an empirically based" side of didactics associated with empirical findings and the "non-empirical" side that is associated with theoretical constructs for understanding the teaching-learning process. The main aim of this article is to revisit research in didactics in German, Nordic and French contexts looking for diversity in the various approaches. This is intended to contribute to the discussion about prospects and shortcomings in the development of a didactics for the intricate subject of vocational education and training. Rather than alternative didactical paths, the article intends to suggest lines of development, encourage discussions and the further research needed concerning relationship didactics and vocational education and training.